2007
DOI: 10.1093/molbev/msm094
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Genome Evolution and Branching Order from Whole Genome Analysis

Abstract: Accurate estimation of any phylogeny is important as a framework for evolutionary analysis of form and function at all levels of organization from sequence to whole organism. Using alignments of nonrepetitive components of opossum, human, mouse, rat, and dog genomes we evaluated two alternative tree topologies for eutherian evolution. We show with very high confidence that there is a basal split between rodents (as represented by the mouse and rat) and a branch joining primates (as represented by humans) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
35
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 52 publications
(63 reference statements)
8
35
0
Order By: Relevance
“…Genome landscape. To establish phylogeny we extended the basic data sampling approach described previously 73 to protein-coding genes, and used established techniques to analyse protein-coding indels 74 and retrotransposon insertions 75 ( Supplementary Notes 19).…”
Section: Methodsmentioning
confidence: 99%
“…Genome landscape. To establish phylogeny we extended the basic data sampling approach described previously 73 to protein-coding genes, and used established techniques to analyse protein-coding indels 74 and retrotransposon insertions 75 ( Supplementary Notes 19).…”
Section: Methodsmentioning
confidence: 99%
“…Among the placental mammals, phylogenetic branching events have been inferred by using either nucleotide sequence data (4)(5)(6)(7)(8)(9)(10)(11) or rare insertion/deletion patterns (12)(13)(14)(15). Many of the results recognize four primary eutherian groups: Afrotheria, Xenarthra, Laurasiatheria, and Euarchontoglires.…”
mentioning
confidence: 99%
“…The Euarchontoglires includes the species from five living mammalian orders (e.g., primates, treeshrews, flying lemurs, rabbits, and rodents). This last group remains the most controversial, and a number of recent studies have suggested it is not valid (4,6,7). The studies that have identified and supported these primary groupings have been able to resolve the branching pattern within some of the clades, but a statistically robust determination of the branching order at the base of the placental clade continues to be elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9). While the morphology studies support the primate-rodent clade (Shoshani and McKenna 1998), the early molecular studies supported the primate-carnivore clade (Graur 1993;Janke et al 1994;Kumar and Hedges 1998; Murphy et al (2001), the phylogeny based on the primate-rodent clade (Madsen et al 2001;Poux et al 2002;Amrine-Madsen et al 2003;Thomas et al 2003;Reyes et al 2004) has become widely accepted, the question is far from being settled: recent studies provided arguments against the primate-rodent clade (Arnason et al 2002;Misawa and Janke 2003;Jorgensen et al 2005;Cannarozzi et al 2007;Huerta-Cepas et al 2007;Huttley et al 2007;Niimura and Nei 2007). Below we analyze some rearrangement-based characters supporting both the primate-carnivore and (to a smaller extent) the primaterodent clade.…”
Section: Comparison Of Infercars and Mgra Reconstructionsmentioning
confidence: 99%